Legal Review of the Use of Crypto Currency as a Means of Payment in Indonesia - Elli Ruslina (Jurnal Info Sains : Informatika dan Sains, 2023)
The rapid growth of financial technology, especially cryptocurrencies, raises challenges and legal questions regarding their acceptance and use in economic transactions. This research aims to examine the legal aspects related to the use of cryptocurrency as a means of payment in Indonesia. This research uses a normative legal approach to laws and regulations relating to cryptocurrencies in Indonesia. The research results show that the use of cryptocurrency, especially Bitcoin, as a means of payment in Indonesia has not been officially recognized. Although regulations such as Bappebti Regulation 7/2020 allow trading of crypto assets on the physical market, cryptocurrency is not considered a legal currency for payment transactions within the country. There are administrative sanctions for Payment Service Providers who violate this provision, and individuals who do not use Rupiah in payment transactions may be punished. Research recommendations include the need for clearer regulations to regulate the legal status of cryptocurrencies, including supervision, taxation and implementation of blockchain in Indonesia. In conclusion, legal recognition and stricter regulations are needed to accommodate the development of cryptocurrencies by considering national economic and financial policies.